Factors associated with ordering food via online meal ordering services. Issue 17 (25th December 2021) - Dana, Liyuwork M; Hart, Ellen; McAleese, Alison; Bastable, Alice; Pettigrew, Simone
Abstract: Objective: Online meal ordering services are increasing in popularity in Australia and globally. Meals ordered online for home delivery are typically less healthy than home-made meals, potentially contributing to weight gain. The aim of the present study was to identify the types of consumers who are most likely to engage in online meal ordering. Design: A cross-sectional survey including items relating to demographic and lifestyle factors was disseminated via a web panel provider. Setting: Australia. Participants: A total of 2010 Australian adults aged 18+ years. Results: More than a quarter of respondents (28 %) engaged in online meal ordering at least once in the previous month. Younger respondents, those with a higher BMI, and those with higher education and income levels were more likely to have done so. Consuming higher levels of sugary drinks and fast-food restaurant patronage were significantly associated with ordering meals online for home delivery. Conclusions: The outcomes of this study suggest that the use of online meal ordering services is becoming a common practice in Australia, and it is therefore important to implement evidence-based strategies and policies to encourage individuals to make healthy food choices when using these services.